EMPLACEMENT AGE OF THE RAOHE COMPLEX IN EASTERN HEILONGJIANG PROVINCE AND THE TECTONIC EVOLUTION OF THE EASTERN PART OF NORTHEASTERN CHINA - Cheng R.Y.; Ge W.C.; Sun D.Y.; Wu F.Y.; Yang J.H.; Liu X.M. (My University, 2006)
Raohe Complex, located in the eastern Heilongjiang Province and composed of deep oceanic sediments and mafic igneous rocks,was considered as slice of oceanic crust and intruded by Hamahe and Taipingeun granites. Zircon U-Pb dating indicated that both of plutons were emplaced in Early Cretaceous, with the Hamahe pluton formed at three individual stages (131Ma, 124Ma and ≈ 115Ma, respectively) and the Taipingcun pluton at 111 - 114Ma. However, the gabbro in Raohe Complex was formed at 166 ± 1Ma, and the latest radiolarian in the deep oceanic sediments is about 160 - 150Ma. Therefore, it is concluded that the emplacement of the Raohe Complex took place at 150 - 131Ma of Late Jurassic-Early Cretaceous, indicating that there existed the Pacific plate subduction and striking-slip in this area before and during Late Jurassic-Early Cretaceous. Petrological studies indicate that both plutons contained magmatic cordierites and show peraluminous characteristics, suggesting their S-type affinity derived from partial melting of the sedimentary rocks. Hf isotopic analyses show that the zircons from plutons have high 176Hf/177Hf ratios and positive εHf(t) values, and the Hf isotope model age with the felsic crust rocks is 500 - 780Ma, which indicates that their protolith should be the juvenile crust formed in Neo Proterozoic-Phanerozoic. Therefore, it is suggested that there existed significant crust uplift and weathering before Late Jurassic-Early Cretaceous in the area.
Keywords: LU-HF ISOTOPE; RAOHE; S-TYPE GRANITE; ZIRCON U-PB DATING; Докембрий::Протерозой; Мезозой::Меловая; Мезозой::Юрская; Precambrian::Proterozoic; Mesozoic::Cretaceous; Mesozoic::Jurassic